RESEARCH ON THE COMPETENCIES OF PRIMARY SCHOOL TEACHERS CONCERNING THE PHYSICAL EDUCATION OF PUPILS - Iv. Prokopov; M. Legurska; V. Mircheva (Trakia Journal of Sciences)
The purpose of the present research is to establish the competencies of the pedagogical specialists working in the system of primary education regarding the methodology of teaching physical culture and to derive the respective conclusions and recommendations.The methodology used in this research is based on inquiry among pedagogical staff. Diagnosing the competencies of primary school teachers on the problem would help to develop and implement a system of methods for raising the qualification of pedagogical specialists on the methodology of teaching physical education in primary schools. The increase of the levels of physical capacity of the students at primary schools directly correlates with the professional training of the pedagogical specialists. The urgency of the problem stems from the fact that in recent years there has been a tendency to increase the levels of hypokinesia among students, which in turn leads to an increase in body mass index and respectively to many diseases of both the musculoskeletal system and internal organs and systems. In conclusion we consider that primary school teachers need a better qualification in the field of physical education.